2001
DOI: 10.1063/1.1383986
|View full text |Cite
|
Sign up to set email alerts
|

Construction scheme for regularized diabatic states

Abstract: A simple construction scheme for quasidiabatic electronic states implemented earlier for a Jahn–Teller situation [J. Chem. Phys. 110, 9371 (1999)] is extended to the case of a seam of symmetry-allowed conical intersections. It is based on the idea of removing only the singular part of the nonadiabatic coupling elements, leading to the notion of “regularized” diabatic states. Explicit working equations are given for the resulting potential energy matrix which require only information from the adiabatic potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
156
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(159 citation statements)
references
References 50 publications
1
156
0
Order By: Relevance
“…Such a warranty is not insured by direct diabatization schemes either providing diabatic wave functions 26,47-51 or diabatic energies. 62,63 The method can be classified as an indirect diabatization procedure that allows a well-defined global zeroth-order solution. In fact, it provides a diabatic grid of points with a proper description of the crossing seams in their full dimensionality, which is key for the study of nonadiabatic processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a warranty is not insured by direct diabatization schemes either providing diabatic wave functions 26,47-51 or diabatic energies. 62,63 The method can be classified as an indirect diabatization procedure that allows a well-defined global zeroth-order solution. In fact, it provides a diabatic grid of points with a proper description of the crossing seams in their full dimensionality, which is key for the study of nonadiabatic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Also for H 2 S, Köppel et al 62 have implemented the diabatization procedure of Thiel and Köppel,28 where the main idea is to remove only the part responsible for the singularities from the nonadiabatic coupling term via a unitary transformation. Their results were compared with those of Simah et al, 49 showing that their diabats do not merge either the adiabats at the HS-S dissociation channel.…”
Section: Global Multisheeted Approaches Employing Diabatization Schemmentioning
confidence: 99%
“…(Such a transformation has also been used fruitfully by other workers, based on other criteria. 37,42 ) In order for this to produce useful diabatic states, it is necessary to first re-express the configuration state functions (CSFs) in terms of diabatic molecular orbitals (DMOs), and these are produced by the fourfold way. The essential step in using the fourfold way to obtain DMOs is maximizing a three-parameter functional that involves the sum of the squares of the orbital occupation numbers for all of the states, a state-averaged natural orbital term, 38 and a transition density term.…”
Section: General Theoretical Considerations and Definitionsmentioning
confidence: 99%
“…It can be shown that this procedure minimizes the 2 norm of the derivative coupling (|d| 2 = min) in the vicinity of the reference point [30]. Other techniques in the same spirit include: enforcing configurational uniformity, so that each diabatic wavefunction is predominantly constructed from a fixed set of electronic configurations [31,32]; regularizing adiabatic states to remove the divergent portion of the coupling [33,34]; and the fourfold way, which combines many of the positive features of the above methods [35,36]. As a starting point, these techniques require a very accurate description adiabatic states and are thus typically used in conjunction with high-level CI calculations.…”
Section: A Deductive Strategiesmentioning
confidence: 99%